Multi‐sited research methodology: Improving understanding of transnational concepts. Issue 3 (27th September 2018) - Jokela‐Pansini, Maaret
Abstract : Research at multiple sites and "talking across worlds" have generally been important in feminist and geographic scholarship. Some studies have examined methodological dilemmas endemic to research involving multiple locations. Other studies have drawn on multi‐sited research including perspectives of participants and researchers beyond a single site. Most of these studies have explored how groups, individuals and discourses move between local and transnational spaces. However, evidence on how such methodologies improve our understanding of transnational concepts is still scarce. This paper draws on two research projects on women's human rights activism in Honduras and South Africa and explores how multi‐sited research improved the understanding of "women human rights defenders." In Honduras, activists in various women's groups have identified themselves as women human rights defenders since the coup d'état in 2009. This identity enabled them to integrate women's rights into a broader international human rights agenda. In South Africa, activists mostly use the term to influence decision‐making at international organisations and to build alliances with activists globally. This multi‐sited research reveals that women's human rights concepts are not "given." Rather, activists' lived experiences on multiple scales shape the way they understand and "translate" such concepts. Abstract : This paper draws on two research projects on women's human rights activism in Honduras and South Africa and shows how multi‐sited research methodologies can improve our understanding of transnational concepts. It reveals that women's human rights concepts are not "given." Rather, activists' lived experiences on multiple scales shape the way they understand and "translate" such concepts.